2006
DOI: 10.1097/01.hjr.0000239465.26132.29
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for participation in leisure-time physical activity and competitive sports of patients with arrhythmias and potentially arrhythmogenic conditions Part II: Ventricular arrhythmias, channelopathies and implantable defibrillators

Abstract: This consensus paper on behalf of the Study Group on Sports Cardiology of the European Society of Cardiology follows a previous one on guidelines for sports participation in competitive and recreational athletes with supraventricular arrhythmias and pacemakers. The question of imminent life-threatening arrhythmias is especially relevant when some form of ventricular rhythm disorder is documented, or when the patient is diagnosed to have inherited a pro-arrhythmogenic disorder. Frequent ventricular premature be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
144
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 76 publications
(97 reference statements)
0
144
0
14
Order By: Relevance
“…According to a prespecified study protocol, we reserved CMR in case of frequent, complex, or exercise‐induced arrhythmias, which are a recognized subgroup with high risk of underlying cardiovascular disease 5, 15, 16, 17. In 3 of these athletes, postcontrast CMR sequences allowed identification of LV LGE with a subepicardial/midmyocardial (ie, nonischemic) pattern, which was not associated with wall motion abnormalities detectable by either echocardiography or cine‐CMR because of its segmental distribution confined to the outer layer of LV musculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a prespecified study protocol, we reserved CMR in case of frequent, complex, or exercise‐induced arrhythmias, which are a recognized subgroup with high risk of underlying cardiovascular disease 5, 15, 16, 17. In 3 of these athletes, postcontrast CMR sequences allowed identification of LV LGE with a subepicardial/midmyocardial (ie, nonischemic) pattern, which was not associated with wall motion abnormalities detectable by either echocardiography or cine‐CMR because of its segmental distribution confined to the outer layer of LV musculature.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies indicating that cardiovascular diseases are more commonly observed in athletes with frequent (>500 PVBs/24 hours), exercise‐induced, or complex VAs, further imaging study by CMR was reserved to athletes fulfilling these arrhythmic criteria, in addition to those with abnormal echocardiographic findings 5, 15, 16, 17. Echocardiography and CMR were also performed in a control group of athletes with no or rare (≤10) isolated PVBs matched with a 1:1 ratio for sex, age class, and type of sport, who volunteered to participate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the 2005 36th Bethesda Conference Guidelines (BCG) recommended that LQTS athletes refrain from participating in most competitive sports if they had a prior history of symptoms attributable to LQTS, QT prolongation >470 ms in males and >480 ms in females, or an implantable cardioverter‐defibrillator (ICD) 6. The European Society of Cardiology, on the other hand, recommended avoiding competitive sports in patients with symptoms and/or corrected QT interval (QTc)>440 to 470 ms in males and 460 to 480 ms in females, those with an ICD, as well as gene carriers with no phenotypic expression 7. As acknowledged by the Bethesda Guidelines Expert Panel, many of the conclusions were made with a “heavy input of ‘what seems reasonable,’” noting that “decision making of this type is often faulty but is the best available.”6 Although exercise restriction may seem a logical approach to minimizing the risk of ventricular arrhythmias and sudden death, in reality this proves more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…C onsensus statements from the American College of Cardiology and European Society for Cardiology [1][2][3] advise against sports participation more vigorous than bowling or golf for patients with implantable cardioverter-defibrillators (ICDs). The bases for these recommendations are postulated risks of failure to defibrillate, injury resulting from loss of control caused by arrhythmia-related syncope or shock, and damage to the ICD system.…”
mentioning
confidence: 99%